The Ni Catalyst Supported on the FSP-made Transition Metal (Co, Mn, Cu or Zn) Doped La2O3 Material for the Dry Reforming of Methane - Phakampai Aunmunkong; Choowong Chaisuk (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
The transition metal (Co, Mn, Cu or Zn) doped La2O3 material was prepared by flame spray pyrolysis (FSP) technique. The 2 wt.% Ni catalyst supported on this material was characterized by XRD, N2 physisorption, TPR, H2 chemisorption and TGA, and evaluated by the dry reforming of methane (DRM). The perovskite structure was certainly formed when either Co or Mn was introduced. The Cu can generate the La2CuO4 spinel phase while the Zn showed a mixed phase of La2O3, ZnO and La(OH)3. The Ni/Co-La2O3 catalyst was more active for the DRM because of high amount of active dual sites of Ni and Co metals dispersed on the catalyst surface. The formation of La2O2CO3 during the reaction can inhibit the coke formation. The cooperation of La2O2CO3 and MnO phases in the Ni/Mn-La2O3 catalyst was promotional effect to decrease carbon deposits on the catalyst surface. The partial substitution of Co for Mn with a small content of Mn can enhance the catalytic activity and the product yield. The Ni/Mn0.05Co0.95-La2O3 catalyst showed the highest CH4 conversion, H2 yield and H2/CO ratio. The Mn inserted into the perovskite structure of LaCoO3 was an important player to change oxygen mobility within the crystal lattice to maintain a high performance of the catalyst. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).